ENGLISHIZATION AND THE DISCURSIVE CONSTRUCTIONS IN SOCIAL MEDIA DISCOURSES OF THE #ENDSARS PROTEST IN NIGERIA - Gabriel B. Egbe (Universitas Widyatama, 2022)
The social media has become a potent digital tool to make strong political and social statements globally especially with the internationalization of English. This has been underscored by the #EndSARS protest in Nigeria. The protest, led mainly by Nigerian youths, remains one of the most sweeping social media activisms in the history of the country. The reverberations and revolts which accompanied the initially peaceful protest have brought to the fore the power of the social media. This study identifies the discursive strategies and semiotic resources deployed during the #EndSARS protest to underscore the role of English in the construction and counter construction of discourses. Using Critical Discourse Studies and Multimodal Discourse Analysis, the paper interrogates about 30 purposefully sampled posts from selected WhatsApp platforms during the protests. The study argues that the social media affords users a platform to communicate without the gatekeeper constraints of mainstream media to create group membership, spread ideologies, and to draw national and global attention using the medium of English to cut across geo-political and linguistic boundaries. The study also reveals that while the initial #EndSARS protest constructs an organized, peaceful, and regenerative group of young Nigerians in search of a better Nigeria, a Nigeria of progressive and savvy minds, the counter discourse celebrates disruption, destruction, and death yielding the negative construction of hoodlums, arsonists, looters, and criminals which the #EndSARS protest was supposed to interrogate and repudiate thus temporarily entrenching the status quo and the mentality of business-as-usual in Nigeria.